A three‐phase symmetric converter in AC electric railway systems for power quality and energy efficient improvement. (28th August 2020) - Li, Linwei; Wu, Mingli
Abstract: This paper proposes a three‐phase symmetric converter that is connected between the power grid and the traction network. It can solve power quality problems such as negative sequence current, reactive power, and harmonics, thus reducing the interaction between the power supply and the user. Moreover, it supports the continuous co‐phase power supply, which can remove all the neutral sections in electric railways, to improve energy utilization. Its control is simple and suitable for electric railways. We discuss the system configuration in detail, including the topology, the calculation of parameters, etc. In addition, the proposed scheme is compared with the traditional traction power supply system, railway power conditioner, and the co‐phase power supply system based on active power compensator, as well as the modular multilevel converter‐based scheme, respectively, to highlight its advantages. We design the control strategy, which consists of the input side and the output side. In the control part, we focus on the special problems for the application of this scheme in traction power supply systems, and propose the control strategy based on the characteristics of the traction load. Simulation is carried out and a 45 kVA low power platform is fabricated and tested to validate the effectiveness of the scheme. The results show that it has nice performance in solving the power quality problems of electric railways. Abstract : The topology of the proposed converter is shown in the black dotted box of Figure. It is connected between the power grid and the traction network, and presents a three‐phase symmetric structure, so it can achieve the balanced grid currents with the same circuit parameters and control strategy for each phase. The input side of the topology adopts multiple structure; a multi‐winding transformer is used in each phase to connect to the power grid, and each secondary winding connects with a BTB converter. The output side adopts the series‐parallel structure. The output of the BTB converter is connected in series, and the output of three‐phase is connected in parallel in order to expand the capacity.